Strategies for Kubang Kerian Nursing College - Ezihaslinda, Ngah; Balan, Kunjambu; Wan Jumani, Fauzi (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
24-25 June 2012. The Consultancy and Training Unit was once again entrusted with a challenging task to carry out a training workshop for thirty one nursing tutors.